Sports as a tool for improving their academic performance for the university entrance study on first year faculty of management studies and commerce students, university of jaffna - Thevananth, J.; Kumaradeepan, V. (university of Jaffna, 2014)
This research paper explores the ways in which sports played an important role in creating opportunities for university entrance. The research addresses sports emerged as a significant force for negotiating obstacles commonly experienced by high school students in Sri Lanka. Ministry of sports started a new four program for develop ten sports. It also aims to achieve a top level in Asian standards in these sports; targeted sports are athletics, netball, swimming, boxing, badminton, judo, shooting, weightlifting, and rugby. “Strong athletic programs have higher test scores and lower drop-outs rates.” Daniel H. Bowen & Collin Hitt , 2013. It is not true that sports undermine the academic performance in Srilankan schools. Researchers analyzed and reviewed the data from the first year students, faculty of management studies and commerce against the achievement of high school sports and the performance in the G.C.E A/L examination. Based on our findings the students' involvement in sports promoted their academic success. There is a positive relationship between the commitment to athletics and academics achievement. We conclude that high school sports performances are a gateway to academic achievement.
Keywords: Sports; Academic performance; School sports